2016
DOI: 10.5937/kgjsci1638097m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of O-alkyl derivatives of dehydrozingerone analogues

Abstract: ABSTRACT. Vanillin and isobuthyl methyl ketone (4-methylpentan-2-one) reacts under Claisen-Schmidt conditions yielding corresponding dehydrozingerone analogue, (E)-1-(4-hydroxy-3-methoxyphenyl)-5-methylhex-1-en-3-one. A small series of its O-alkyl derivatives was prepared by alkylation of free phenolic group with corresponding alkyl halides. Products had been tested for their biological activity and demonstrated relatively strong in vitro antimicrobial activity towards different strains of bacteria and fungi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…2,4,[9][10][11] However, the substitution in the aromatic ring of the compound with an aminomethyl group via Mannich reaction has not been reported yet. In this study, a series of five novel Mannich bases of DHZ (2a-e) was synthesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[9][10][11] However, the substitution in the aromatic ring of the compound with an aminomethyl group via Mannich reaction has not been reported yet. In this study, a series of five novel Mannich bases of DHZ (2a-e) was synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Various chemical modification of DHZ has been performed to exploit for diverse biological activities of DHZ derivatives, such as esterification or alkylation of OH phenolic group, replacement of OH with other substituents, substitution of the methoxy group, reduction of double bond, cyclization of α,β-unsaturated carbonyl, and substitution of hydrogen atom bound to the carbonyl α-carbon. 2,4,[9][10][11] Some Mannich bases of DHZ have been synthesized and reported to have better anti-inflammatory activity compared to DHZ and fairly good anti-inflammatory activity compared to indomethacin. However, the aminomethyl group was substituted at the carbonyl α-carbon of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the new vanillin based chalcone analogs were synthesized in very good yields according to the procedures earlier described (18). Compound (CH1) was prepared by Claisen-Schmidt condensation of natural product vanillin and 4methylpentan-2-one.…”
Section: Resultsmentioning
confidence: 99%
“…1) on human colorectal carcinoma cell line (HCT-116) and healthy MRC-5 cell line. CH1 and CH2 were previously synthesized by Muökinja et al (18) and their antibacterial and antifungal activity was confirmed. As referent substances, we used cisplatin (cisPt) for which it was shown to exhibit an effective antitumor effect on different cancer cell lines (19,20) and dehydrozingerone (DHZ) (21-23) which chemical structure is most similar with chemical structure of our investigated chalcones.…”
mentioning
confidence: 99%
“…Keeping in mind the reactivity of phenolic functional group, the synthesis of O-alkyl dehydrozingerone derivatives was carried out as a simple reaction free phenolic group in the boiling acetone solution in the presence of corresponding alkyl halide. Two alkyl derivatives, 4-(3-methoxy-4-propoxyphenyl)-3-buten-2-ones (2a) and 4-(4-butoxy-3-methoxyphenyl)-3-buten-2--ones (2b), were obtained, according to the described literature procedures [17] (Scheme 1).…”
Section: Chemistry Synthesismentioning
confidence: 99%